BEBERAPA SIFAT SPESIFIK ANDISOL UNTUK PEMBEDA KLASIFIKASI PADATINGKAT SERI: STUDI KASUS DI DAERAH CIKAJANG DAN CIKOLE, JAWA BARAT - D. Djaenudin (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2004)
The objective of this research was to study specific soil characteristics of Andisols as series differentiae. Five pedons of Cikajang and Cikole regions were studied. Both regions belong to the wet climate, udic soil moisture regime and isothermic temperature regime. As much as 32 soil samples were taken for analysis of physical, chemical and mineralogical properties follows the standard procedures of The Central Research and Development of Soil and Agroclimate laboratory. The specific soil properties can be used for soil series to differentiate each soil family. In soil family level, pedon Dn-1, Dn-2, and Dn-4 are classified as Typic Hapludand, medial-mixed, isothermic, and pedon Dn-3 and Dn-5 are classified as Thaptic Hapludand, medial-mixed, isothermic. Each soil family consists of two soil series. The properties of buried soil, color, texture, and soil reaction are used for soil series differentiate. Keywords: Andisols, soil series, specific soil characteristics, West Java